From old school to influencers, through confinement and facilitators: Notes for thinking about student subjectivity. (Palimpsesto, 2025)
The text establishes a path that suggests an analysis of student subjectivity. It is, by the way, a way of facing education in a broad sense and that has a direct dialogue with the ways in which young people relate to knowledge and formative instances. First, the educational experience that took place during the confinement as a result of Covid-19 is analyzed. From there, and in a second key, the work of Mark Fisher is reviewed to address the unique characteristics of educational institutions in the context of post-disciplinary societies or societies of control. At this point, some aspects of student subjectivity are noted that are related, on the one hand, to a loss of sense of education as a tool for a future project and, on the other hand, to a certain manifestation of discomfort that manifests itself in at least two expressions: depressive hedonia and postlexia. Both phenomena show a contract of meaning with the current moment of capitalism and therefore with its technical communication regime. Finally, the last section deals with the advance of new formative instances proper to the predominance of the digital world. Elian Chali's writings outline some attempts on new forms of subjectivity linked to education and the expectations projected on it.
Keywords: pandemic; school area; Societies of Control; Student Subjectivity; Influencers